Reducing the Risk of Adverse Events in Patients with Type 2 Diabetes Who are Poorly Treated with Metformin Combined with Acarbose：Dipeptidyl Peptidase-4 Inhibitor is Better Than Insulin - SU Peng, LIU Yukun, LIANG Xiaohua, LIU Xin, YU Yaohui, HUANG Pengfei, BAI Yuru, HE Xiaoyan, SHEN Zhihong, MA Dong (Zhongguo quanke yixue, 2022)
BackgroundClinically, when metformin (Met) combined with acarbose (Aca) cannot achieve the ideal hypoglycemic effect, a third drug will be usually added, such as insulin (Ins) or dipeptidyl peptidase-4 inhibitor (DPP-4i) etc., but there are few reports on the effect of triple therapy on complications related to type 2 diabetes (T2DM) .ObjectiveTo explore the risk of adverse events of DPP-4i combined with Met and Aca, Ins combined with Met and Aca in the treatment of T2DM patients, in order to provide help for the choice of drugs for clinical T2DM treatment.MethodsIn the retrospective cohort study, patients diagnosed with T2DM and treated with Met+Aca+ DPP-4i or Met+Aca+Ins in Shijiazhuang Second Hospital from November 1, 2017 to August 1, 2020 were selected as the study subject. Telephone follow-up was conducted from November 20, 2017 to August 4, 2020, the follow-up wasn't terminated until a preset outcome occurred, then that was recorded. The three prespecified outcome events were non-fatal cardiovascular disease, death from all causes, and severe hypoglycemic events. The comprehensive outcome events including all-cause death, or composite non-fatal cardiovascular events, or severe hypoglycemic events. Propensity score matching (1∶1 ratio for data matching, caliper value set to 0.02) was used, and multivariate Cox proportional hazards regression model was used to analyze the risk of comprehensive outcome events in T2DM patients after drug treatment. Stratified analysis was performed on the effect of each covariate on the risk of comprehensive outcome events in patients treated with different drugs.ResultsFinally, 1 570 patients with T2DM were enrolled, including 1 089 patients who received Met+Aca+Ins treatment (Met+Aca+Ins group) and 481 patients who received Met+Aca+DPP-4i treatment (Met+Aca+DPP-4i group) . There were 434 cases in both groups after propensity score matching. Compared with the Met+Aca+Ins group, the incidences of comprehensive outcome events (6.53/100 person-per year) , non-fatal cardiovascular disease (5.03/100 person-years) , all-cause death (0.73/100 person-per year) , and severe hypoglycemic (0.73/100 person-er year) were lower in the Met+Aca+ DPP-4i group. The multivariate Cox proportional hazards regression model analysis showed that the risk of comprehensive outcome events in the Met+Aca+DPP-4i group was 67% lower than the Met+Aca+Ins group 〔HR=0.34, 95%CI (0.23, 0.50) , P<0.001〕, the risk of composite non-fatal cardiovascular disease decreased by 52% compared with the Met+Aca+Ins group 〔HR=0.48, 95%CI (0.30, 0.77) , P=0.002〕, and the risk of all-cause mortality was higher than the Met+Aca group. The Met+Aca+Ins group group decreased by 81% 〔HR=0.19, 95%CI (0.07, 0.56) , P=0.003〕, and the risk of severe hypoglycemia decreased by 80% compared with the Met+Aca+Ins group 〔HR=0.20, 95%CI ( 0.07, 0.59) , P=0.003〕. The survival curve was drawn with the comprehensive outcome events as the outcome event. The results of Log-rank test showed that the survival rate of Met+Aca+DPP-4i group was higher than the Met+Aca+Ins group (χ2=32.849, P<0.001) . The results of covariate interaction analysis showed that in patients with adequate sleep (>7 h/d) , non-smoking, and no family history of cardiovascular disease, Met+Aca+DPP-4i treatment reduced the incidence of comprehensive outcome events in T2DM patients compared with Met+Aca+Ins treatment (P values were 0.008, 0.031, and 0.042, respectively) .ConclusionAfter failure treatment of Met and Aca in T2DM patients, the supplementation of DPP-4i was associated with a lower risk of comprehensive outcome events, cardiovascular disease, all-cause mortality, and severe hypoglycemia compared with the Ins addition, particularly in patients with adequate sleep, no smoking, and without family history of cardiovascular disease.